Examining the Gendered Effect of Experienced and Vicarious Victimization: A General Strain Theory Perspective - Lee, Yeungjeom (American journal of criminal justice, 2018)
Although general strain theory has broadened our theoretical perspectives, there remains a need to learn about the relationship between victimization and violence. In addition, studies applying general strain theory have yielded mixed findings about gender issues. Using data from the National Survey of Adolescents (NSA), the current study examined the effects of violent victimization on violent offending by gender. More specifically, the study assessed the relationship between two types of victimization (experienced and vicarious) and three types of violent offending (gang fights, robbery, and assault) and investigated whether gender plays a role in the association. Findings of negative binomial regression analyses offered overall support for experienced and vicarious victimization as predictors of violence. However, gendered effects of experienced and vicarious victimization on violence were not supported by results. Interaction effects between gender and victimization were only significant in baseline models (without control factors), however, became insignificant in full models. The implications of these results and limitations were discussed.